Modified asphalt for heavy-load road surface and preparation method thereof
By forming an interlocking cross-linking structure in the asphalt and adding high-performance raw materials, the problem of performance changes in asphalt under extreme temperature conditions is solved, and the thermal stability and compressive strength of asphalt are significantly improved, which extends the service life of the road and improves driving safety.
Patent Information
- Application Number
- CN202411638294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-16
AI Technical Summary
Asphalt is prone to performance changes under extreme temperature conditions, resulting in damage such as cracks and ruts on the road, which seriously affects the driving safety and service life of the road.
Modified ethylene-vinyl acetate copolymer is used to form an interlocking crosslinking structure with asphalt, and high-performance raw materials such as mullite powder, polyphosphoric acid, alkyl glycosides and itaconic anhydride are added to improve the thermal stability and compressive strength of asphalt through chemical bonds and physical filling.
It significantly improves the thermal stability and compressive strength of asphalt, so that the road surface can maintain excellent stability under high temperature and heavy load conditions, extends the service life of the road and improves driving safety.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of road construction materials, and more specifically, to a modified asphalt for heavy-load pavement and a preparation method thereof. Background Art
[0002] Asphalt, as an indispensable key material in the field of road construction, its physical and mechanical properties directly determine the service life and driving safety of the road surface. Especially in heavy-load traffic environments, the road surface needs to withstand huge load impacts from heavy vehicles and continuous friction and wear. As a viscoelastic-plastic material, although it has certain flexibility and adhesion, its performance is easily affected by both ambient temperature and load.
[0003] In the hot summer, as the ambient temperature continues to rise, the asphalt material will soften significantly, and this change will seriously weaken the overall stability of the asphalt mixture. When the road surface is repeatedly rolled by heavy-loaded vehicles, the softened asphalt cannot effectively resist the indentation of the wheels, resulting in rutting, shifting and other damage to the road surface, which seriously affects the flatness and driving safety of the road.
[0004] In the case of a sudden drop in temperature or long-term low temperatures in winter, asphalt will become hard and brittle, and its ability to adapt to deformation will be greatly reduced. At this time, the road surface is more likely to crack and suffer functional damage under the combined influence of heavy vehicle loads and temperature stress. These cracks will not only further weaken the structural strength of the road surface, but also accelerate the intrusion of moisture and other harmful substances, thereby accelerating the aging process of the road surface and shortening its service life.
[0005] In summary, the thermal stability of asphalt has always been a technical problem that needs to be solved in the field of road construction. Asphalt with poor thermal stability is prone to performance changes under extreme temperature conditions, resulting in cracking, rutting and other damage to the road surface, which seriously affects the driving safety and service life of the road. Therefore, it is necessary to continue to develop a modified asphalt that can effectively improve the thermal stability of asphalt. Summary of the invention
[0006] In order to improve the thermal stability of asphalt, the present application provides a modified asphalt for heavy-load pavement and a preparation method thereof.
[0007] In the first aspect, the present application provides a modified asphalt for heavy-load pavement, which adopts the following technical solution:
[0008] A modified asphalt for heavy-load pavement, comprising the following raw materials in parts by weight:
[0009] 0.5-1.2 parts of polyphosphoric acid, 8-10 parts of modified ethylene-vinyl acetate copolymer, 70-80 parts of base asphalt, 3-5 parts of curing agent, 1-3 parts of alkyl glycoside, 9-12 parts of mullite powder, and 2-3 parts of itaconic anhydride.
[0010] By adopting the above technical solution, the modified ethylene-vinyl acetate copolymer has good compatibility with asphalt and can be evenly dispersed in asphalt. The ethylene-vinyl acetate copolymer has good elasticity and toughness and can react with the alkaline groups on the surface of asphalt to form a stable chemical bond, thereby enhancing the overall stability of the material. The light components in the asphalt are absorbed between the molecular chains of the modified ethylene-vinyl acetate copolymer (EVA), causing the modified ethylene-vinyl acetate copolymer to swell, and the two undergo a cross-linking reaction to form an interlocking cross-linked structure of EVA and asphalt, thereby improving the thermal stability and compressive strength of the asphalt.
[0011] As a high-performance inorganic filler, mullite powder can be tightly filled in the gaps of asphalt due to its tiny particle size and unique crystal structure, forming a denser structure, thereby greatly improving the compressive strength and modulus of asphalt. It can also work synergistically with EVA to jointly improve the thermal stability and mechanical properties of asphalt.
[0012] Polyphosphoric acid can enhance the grafting effect between EVA and asphalt, thereby helping the modified asphalt and EVA to build a tighter and more stable spatial network structure, so that the modified asphalt can effectively resist deformation caused by external loads and temperature changes, and improve the thermal stability and compressive strength of the modified asphalt. Alkyl polyglycoside, as a surfactant, can improve the wettability between asphalt and aggregate, and improve the uniformity and stability of asphalt mixtures. Itaconic anhydride, as an organic anhydride, can react with certain functional groups in asphalt to form a more stable chemical bond. This chemical bonding can not only improve the weather resistance and aging resistance of asphalt, but also improve the rheological properties of asphalt to a certain extent, and further improve the compressive strength of asphalt.
[0013] Optionally, the modified ethylene-vinyl acetate copolymer comprises the following raw materials in parts by weight: 0.1-0.4 parts of catalyst, 6-8 parts of polyurethane, 2-3 parts of polydopamine, 0.5-0.8 parts of dicumyl peroxide, 10-14 parts of ethylene-vinyl acetate copolymer, and 16-20 parts of toluene.
[0014] Optionally, the modified ethylene-vinyl acetate copolymer is prepared by the following steps:
[0015] Take ethylene-vinyl acetate copolymer and add it to toluene, heat the oil bath to 60-80°C and stir to dissolve, add catalyst and dicumyl peroxide, continue to heat to 80-90°C, then add polyurethane and polydopamine and stir to mix, react for 4-5 hours and stop, to obtain the modified ethylene-vinyl acetate copolymer.
[0016] By adopting the above technical solution, ethylene-vinyl acetate copolymer can be modified to improve the thermal stability of asphalt, but in actual application, the penetration of water will affect its thermal stability, so it is further modified by using polyurethane with good waterproof performance, and the EVA molecular chain undergoes cross-linking and grafting reaction with the added polyurethane and polydopamine molecular chains to form a modified EVA with a more complex structure, which not only improves the waterproof performance of ethylene-vinyl acetate copolymer, but also further improves its stability and avoids decomposition and oxidation in high temperature and high humidity environments. Furthermore, polyurethane has good ductility and can adapt to the natural expansion and contraction of asphalt caused by temperature changes or stress, thereby further improving the thermal stability of asphalt.
[0017] Optionally, the catalyst is an organotin catalyst.
[0018] By adopting the above technical solution, the organotin catalyst can not only promote chain growth in the polymerization reaction, but also affect the chain structure and molecular weight distribution of the polymer. By selecting a suitable organotin catalyst, the molecular structure and properties of the modified ethylene-vinyl acetate copolymer can be regulated, and the flexibility and heat resistance of the polymer can be improved, thereby further meeting the special requirements of heavy-duty road modified asphalt for polymer performance.
[0019] Optionally, the particle size of the mullite powder is 10-20 mm.
[0020] By adopting the above technical solution, the addition of mullite powder, on the one hand, as a filler, utilizes its good mechanical properties as a supporting point in the asphalt material, thereby improving the compressive strength of the material. At the same time, mullite has high thermal stability and good thermal conductivity. It can effectively conduct and disperse the heat through uniform dispersion in the network structure. The mullite powder with a particle size of 10-20mm is selected because it has better dispersion stability and plays a better role in improving the asphalt material.
[0021] Optionally, the curing agent is sulfur.
[0022] By adopting the above technical solution, sulfur as a curing agent can interact with asphalt molecular chains to form crystals. These crystals can significantly enhance the structural strength of asphalt and improve the bearing capacity of the road surface. At the same time, sulfur can also serve as an effective cross-linking agent to form chemical bonds between EVA molecular chains and increase the cross-linking degree of the material, thereby further improving the mechanical properties and thermal stability of the asphalt material.
[0023] Optionally, the raw materials further include 1-3 parts of pentaerythritol stearate.
[0024] By adopting the above technical solution, pentaerythritol stearate, as a large molecular weight liquid grease, has good lubricity and fluidity. Adding an appropriate amount of pentaerythritol stearate to asphalt can reduce the viscosity of asphalt, making it easier to construct and lay. At the same time, it can also improve the uniformity of asphalt mixture, help the raw materials such as mullite powder and EVA in asphalt to be evenly dispersed in asphalt, and prepare asphalt with better thermal stability and higher compressive strength.
[0025] In a second aspect, the present application provides a method for preparing modified asphalt for heavy-duty pavement, using the following technical solution:
[0026] A method for preparing modified asphalt for heavy-load pavement comprises the following steps:
[0027] The base asphalt is heated to 160-170°C, and then modified ethylene-vinyl acetate copolymer, itaconic anhydride and polyphosphoric acid are added to the melted asphalt. After continuing to stir the reaction for 1-2 hours, mullite powder, alkyl glycoside and curing agent are added, followed by high-speed shear stirring for 30-60 minutes at a stirring speed of 3500-4000 r / min to obtain the modified asphalt.
[0028] By adopting the above technical solution, modified asphalt with good thermal stability and strong compressive resistance can be obtained.
[0029] In summary, this application has the following beneficial effects:
[0030] 1. Since the present application uses ethylene-vinyl acetate copolymer which has good compatibility with asphalt to modify asphalt, the ethylene-vinyl acetate copolymer can be evenly dispersed in the matrix asphalt to react with the asphalt to form an interlocking cross-linked structure, making full use of its good thermal stability, thereby improving the thermal stability and compressive strength of the asphalt.
[0031] 2. In this application, modified ethylene-vinyl acetate copolymers that have undergone specific modification treatments are preferred, and high-performance raw materials such as polyphosphoric acid and mullite powder are added. The modified asphalt can maintain excellent stability under high temperature and heavy load conditions. The interlocking cross-linked structure of EVA and asphalt, the tight filling of mullite powder, and the grafting enhancement of polyphosphoric acid jointly improve the thermal stability and compressive strength of asphalt, allowing the road surface to withstand greater loads and temperature changes without significant deformation or damage. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0034] SK-90 base asphalt has a needle penetration of 94.5 mm, a softening point of 47.3 °C, and a density of 1.004 g / cm 3 , 15℃ elongation greater than 150; ethylene-vinyl acetate copolymer was purchased from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd., brand: EV180; polyurethane was purchased from Laiyang Shengbang Silicone Technology Co., Ltd., model: SI-2045, viscosity 500-1000mpa·s.
[0035] Preparation examples of raw materials and / or intermediates
[0036] Preparation Example 1
[0037] A modified ethylene-vinyl acetate copolymer, the preparation of which comprises the following steps:
[0038] Take 10 kg of ethylene-vinyl acetate copolymer and add it to 16 kg of toluene, turn on the stirring device, heat the oil bath to 70 ° C and continue stirring until the EVA is dissolved, add 0.2 kg of dibutyltin dilaurate (catalyst) and 0.65 kg of diisopropylbenzene peroxide, continue to heat to 90 ° C, add 7 kg of polyurethane and 2.5 kg of polydopamine, stir and mix, stop heating after reacting for 4 hours, and naturally cool to room temperature to obtain the modified ethylene-vinyl acetate copolymer.
[0039] Preparation Example 2
[0040] A modified ethylene-vinyl acetate copolymer, the preparation of which comprises the following steps:
[0041] Take 12 kg of ethylene-vinyl acetate copolymer and add it to 18 kg of toluene, turn on the stirring device, heat the oil bath to 60 ° C and continue stirring until the EVA is dissolved, add 0.1 kg of dibutyltin dilaurate (catalyst) and 0.5 kg of diisopropylbenzene peroxide, continue to heat to 90 ° C, add 8 kg of polyurethane and 3 kg of polydopamine, stir and mix, stop heating after reacting for 4 hours, and naturally cool to room temperature to obtain the modified ethylene-vinyl acetate copolymer.
[0042] Preparation Example 3
[0043] A modified ethylene-vinyl acetate copolymer, the preparation of which comprises the following steps:
[0044] Take 14 kg of ethylene-vinyl acetate copolymer and add it to 20 kg of toluene, turn on the stirring device, heat the oil bath to 80 ° C and continue stirring until the EVA is dissolved, add 0.4 kg of dibutyltin dilaurate (catalyst) and 0.8 kg of diisopropylbenzene peroxide, continue to heat to 90 ° C, add 6 kg of polyurethane and 2 kg of polydopamine, stir and mix, stop heating after reacting for 4 hours, and naturally cool to room temperature to obtain the modified ethylene-vinyl acetate copolymer.
[0045] Preparation Example 4
[0046] A modified ethylene-vinyl acetate copolymer is different from Preparation Example 1 in that the catalyst used in this Preparation Example is an organic acid catalyst phosphoric acid.
[0047] Comparative Preparation Example 1
[0048] A modified ethylene-vinyl acetate copolymer is prepared according to the method in Preparation Example 1, except that polydopamine is not added during the modification process.
[0049] Comparative Preparation Example 2
[0050] A modified ethylene-vinyl acetate copolymer is prepared according to the method in Preparation Example 1, except that no polyurethane is added during the modification process.
[0051] Example
[0052] Example 1
[0053] A modified asphalt for heavy-load pavement, the preparation of which comprises the following steps:
[0054] Heat 75 kg of base asphalt to 160°C to melt, then add 9 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 2 kg of itaconic anhydride, and 1.2 kg of polyphosphoric acid to the melted asphalt, continue stirring and reacting for 2 hours, then add 11 kg of mullite powder, 3 kg of alkyl glycoside and 3 kg of sulfur, then high-speed shear stirring for 30 minutes at a stirring speed of 4000 r / min to obtain the modified asphalt; the particle size of the added mullite powder is 10-20 mm.
[0055] Example 2
[0056] A modified asphalt for heavy-load pavement, the preparation of which comprises the following steps:
[0057] 70 kg of base asphalt was heated to 170°C to melt, and then 8 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 3 kg of itaconic anhydride, and 0.85 kg of polyphosphoric acid were added to the melted asphalt. After continuing to stir and react for 1.5 hours, 12 kg of mullite powder, 2 kg of alkyl glycoside and 4 kg of sulfur were added, followed by high-speed shear stirring for 30 minutes at a stirring speed of 3500 r / min to obtain the modified asphalt; the particle size of the added mullite powder was 10-20 mm.
[0058] Example 3
[0059] A modified asphalt for heavy-load pavement, the preparation of which comprises the following steps:
[0060] Heat 80kg of base asphalt to 170°C to melt, then add 10kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 2.5kg of itaconic anhydride, and 0.5kg of polyphosphoric acid to the melted asphalt, continue stirring and reacting for 2 hours, then add 9kg of mullite powder, 1kg of alkyl glycoside and 5kg of sulfur, followed by high-speed shear stirring for 30 minutes at a stirring speed of 4000r / min to obtain the modified asphalt; the particle size of the added mullite powder is 10-20mm.
[0061] Example 4
[0062] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Preparation Example 2 is used in this example.
[0063] Example 5
[0064] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Preparation Example 3 is used in this example.
[0065] Example 6
[0066] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Preparation Example 4 is used in this example.
[0067] Example 7
[0068] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the particle size of the mullite powder used in this example is 25-30 mm.
[0069] Example 8
[0070] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the particle size of the mullite powder used in this example is 1-10 mm.
[0071] Example 9
[0072] A modified asphalt for heavy-load pavement, which is different from Example 1 in that 1 kg of pentaerythritol stearate is further added in this example, and the preparation comprises the following steps:
[0073] Heat 75 kg of base asphalt to 160°C to melt, then add 9 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 2 kg of itaconic anhydride, and 1.2 kg of polyphosphoric acid to the melted asphalt, continue stirring and reacting for 2 hours, then add 11 kg of mullite powder, 1 kg of pentaerythritol stearate, 3 kg of alkyl glycoside and 3 kg of sulfur, then high-speed shear stirring for 30 minutes at a stirring speed of 4000 r / min to obtain the modified asphalt; wherein the particle size of the added mullite powder is 10-20 mm.
[0074] Example 10
[0075] A modified asphalt for heavy-load pavement, which is different from Example 9 in that 3 kg of pentaerythritol stearate is added in this example.
[0076] Comparative Example
[0077] Comparative Example 1
[0078] A modified asphalt for heavy-load pavement, which is different from Example 1 in that in this comparative example, an equal amount of unmodified ethylene-vinyl acetate copolymer is used to replace the modified ethylene-vinyl acetate copolymer.
[0079] Comparative Example 2
[0080] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Comparative Preparation Example 1 is used in this comparative example.
[0081] Comparative Example 3
[0082] A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Comparative Preparation Example 2 is used in this comparative example.
[0083] Comparative Example 4
[0084] A modified asphalt for heavy-load pavement, which is different from Example 1 in that no alkyl glycoside is added in this comparative example 1.
[0085] Comparative Example 5
[0086] A modified asphalt for heavy-load pavement, which is different from Example 1 in that polyphosphoric acid is not added in this comparative example 1.
[0087] Performance testing
[0088] Detection method / test method
[0089] Thermal stability: The Marshall stability test was carried out in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTKG / E20-2011). The MTS universal testing machine was used to perform a four-point bending fatigue test. The complete fracture of the asphalt material was used as the failure standard to test the stability of the asphalt prepared by the above-mentioned mixture preparation method. The test results are shown in Table 1. Compressive strength: The test was carried out in accordance with JTJ 052-2000 "Specifications for Construction and Acceptance of Asphalt Pavement for Highway Engineering".
[0090] Table 1 Test results
[0091] Marshall stability / KN Compressive strength / MPa Example 1 15.52 7.92 Example 2 15.21 7.87 Example 3 14.95 7.85 Example 4 15.11 7.75 Example 5 15.37 7.88 Example 6 14.21 7.51 Example 7 13.51 7.25 Example 8 13.28 7.17 Example 9 16.15 8.26 Example 10 16.29 8.33 Comparative Example 1 12.13 5.91 Comparative Example 2 13.56 6.87 Comparative Example 3 13.16 6.65 Comparative Example 4 14.01 6.84 Comparative Example 5 13.66 6.21
[0092] Combining Examples 1-3 and Comparative Examples 1-3 and Table 1, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Examples 1-3, indicating that the modified asphalt with better thermal stability and higher compressive strength can be obtained by modifying ethylene-vinyl acetate copolymer using the method of the present application and then adding asphalt. Combining Example 1 with Comparative Examples 2-3, it can be seen that the use of polydopamine and polyurethane to modify ethylene-vinyl acetate copolymer can improve its waterproof performance and stability, and can promote cross-linking and grafting reactions, further improve its stability, thereby improving the thermal stability and compressive strength of the modified asphalt.
[0093] Combining Examples 1-3 and Comparative Example 4 and Table 1, it can be seen that the test data of Examples 1-3 are better than those of Comparative Example 4, indicating that alkyl glycosides can synergistically act with other substances in the raw materials to improve the wettability between asphalt and other raw materials, improve the uniformity of asphalt, and thus further improve the compressive strength of asphalt.
[0094] Combining Examples 1-3 and Comparative Example 5 and Table 1, it can be seen that the test data of Examples 1-3 are better than those of Comparative Example 5, indicating that polyphosphoric acid can enhance the network structure constructed between asphalt and EVA, so that the modified asphalt can effectively resist deformation caused by external loads and temperature changes, and improve the thermal stability and compressive strength of the modified asphalt.
[0095] It can be seen from Examples 1-6 and Table 1 that the experimental data of Examples 1-5 are better than those of Example 6, indicating that the choice of catalyst in the modification process of ethylene-vinyl acetate copolymer affects its modification effect. The selection of organic tin catalyst can not only promote the occurrence of modification reaction but also further regulate the molecular structure and properties of modified ethylene-vinyl acetate copolymer, improve the flexibility and heat resistance of the polymer, and thus improve the thermal stability of modified asphalt.
[0096] Combining Example 1 with Examples 7-8 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Examples 7-8, indicating that the particle size of the added mullite powder will affect the final performance of the asphalt. Selecting mullite powder with a suitable particle size can be evenly dispersed in the asphalt material, serving as a support point to improve the compressive strength and heat resistance stability of the material.
[0097] Combining Example 1 with Examples 9-10 and Table 1, it can be seen that the experimental data of Examples 9-10 are better than those of Example 1, indicating that the addition of pentaerythritol stearate can evenly distribute the various components in the asphalt and improve the uniformity of the asphalt mixture, thereby obtaining asphalt with good thermal stability and high compressive strength.
[0098] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A modified asphalt for heavy-load pavement, characterized in that: The composition comprises the following raw materials in parts by weight: 0.5-1.2 parts of polyphosphoric acid, 8-10 parts of modified ethylene-vinyl acetate copolymer, 70-80 parts of base asphalt, 3-5 parts of curing agent, 1-3 parts of alkyl glycoside, 9-12 parts of mullite powder, 2-3 parts of itaconic anhydride; The modified ethylene-vinyl acetate copolymer is prepared by the following steps: Add ethylene-vinyl acetate copolymer to toluene, heat the oil bath to 60-80° C., stir and dissolve, add catalyst and dicumyl peroxide, continue to heat to 80-90° C., add polyurethane and polydopamine, stir and mix, react for 4-5 hours and then stop, to obtain the modified ethylene-vinyl acetate copolymer; The modified ethylene-vinyl acetate copolymer comprises the following raw materials in parts by weight: 0.1-0.4 parts of catalyst, 6-8 parts of polyurethane, 2-3 parts of polydopamine, 0.5-0.8 parts of dicumyl peroxide, 10-14 parts of ethylene-vinyl acetate copolymer and 16-20 parts of toluene.
2. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The catalyst is an organotin catalyst.
3. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The particle size of the mullite powder is 10-20 mm.
4. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The curing agent is sulfur.
5. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The raw materials also include 1-3 parts of pentaerythritol stearate.
6. A method for preparing modified asphalt for heavy-load pavement according to any one of claims 1 to 4, characterized in that: The steps include: The base asphalt is heated to 160-170°C, and then modified ethylene-vinyl acetate copolymer, itaconic anhydride and polyphosphoric acid are added to the melted asphalt. After continuing to stir the reaction for 1-2 hours, mullite powder, alkyl glycoside and curing agent are added, followed by high-speed shear stirring for 30-60 minutes at a stirring speed of 3500-4000 r / min to obtain the modified asphalt.
Citation Information
Patent Citations
Preparation method of environment-friendly asphalt mixture additive
CN106147252A
Sound-proof modified asphalt waterproof roll and preparation method thereof
CN107641327A